Physicochemical, rheological and structural properties of flours from six quinoa cultivars grown in Colombia - García-Parra, Miguel; Polo-Muñoz, María Paula; Nieto Calvache, Jhon Edinson; Agudelo-Laverde, Lina Marcela; Roa-Acosta, Diego Fernando (Frontiers in Sustainable Food Systems, 2022)
Background: Inclusion of quinoa in the diet of consumers has generated a challenge for quinoa producers and food processors, which involves the study of new cultivars and the functional properties of their flours. Methods: Six quinoa cultivars (Titicaca, Blanca real, Soracá, Pasankalla, Puno and Nariño) were analyzed for their proximate composition using the methodologies proposed by the Association of Official Analytical Collaboration, AOAC. A rheological analysis was carried out with flours from each cultivar. A sequential test including a flow test, a pasting test and another flow test was programmed to evaluate the flow behavior before and after a heating process. In addition, the structural properties of the cultivar flours were evaluated by Fourier Transform Infrared spectroscopy (FTIR). Results: It was found that the Pasankalla, Titicaca and Soracá cultivars had a higher (p<0.05) protein content, while the Puno, Pansakalla and Blanca real cultivars stood out for their higher (p<0.05) lipid content. On the other hand, it was found that before heating, all quinoa flour dispersions had a dilatant flow (n>1), but after heating, all of them showed a decrease of index values, where the flours of the Titicaca and Pasankalla cultivars were more affected with a tendency towards a Newtonian flow (n≈1). The pasting test showed that the viscosity varied according to the cultivar tested. It is noteworthy that both Titicaca and Soracá presented a high peak viscosity (0.16 ± 0.01 and 0.13 ± 0.02 Pa·s respectively) and different setback values on cooling (0.100 ± 0.028 and 0.01 ± 0.01 Pa·s respectively). Spectroscopic analysis showed a direct relationship between the intensity of the peaks and the nutritional content of the flours. In addition, secondary protein structures such as β-sheet, β-Turn, α-Helix and Random Coil were identified after deconvolution of the spectra. The differences in the protein structures of each cultivar could allow their identification by this methodology. Conclusions: It can be concluded that quinoa flours from the six cultivars could be used for the formulation of different food products, such as beverages, baked goods, snacks, pasta and others, acting as nutritional improvers and modifiers of rheological, textural and functional properties